A few drops of bitters - McKevett, G. A. (McKevett, G. A. Savannah Reid mystery., 2022)
"Between being a mom to her new foster son and arranging a lavish wedding for her sister, things are messy, unpredictable, and delightfully fulfilling for Savannah these days. She even gains an impressive friend: Dr. Carolyn Erling, a caring veterinarian with a deeper story than her down-to-earth nature suggests. When Savannah attends a birthday bash for Dr. Carolyn's husband, she's astonished to find that her no-frills acquaintance resides in a pristine hilltop mansion with Dr. Stephen Erling, a jet-setter brain surgeon boasting throngs of A-list patients around the globe. Before Savannah can get a headcount on the mingling celebrities, Dr. Stephen has one too many champagne toasts and drops dead. With a poisonous residue found inside Dr. Stephen's glass, the search is on for the killer who spiked his drink. Motivated to set things right for a devastated Dr. Carolyn, Savannah must infiltrate the elite world of foreign dignitaries and Oscar-winning stars to identify the guilty culprit--or prepare to kiss this happy chapter in her life goodbye." -- Amazon.